Trends And Issues Of TPACK Research In The Last 10 Years: A Bibliometric Analysis - Melsya Shalsabila; Misbahul Jannah (JKA, 2025)
This study aims to analyze current trends and issues in TPACK (Technological Pedagogical and Content Knowledge) research over the past ten years through bibliometric analysis. The Data used in the study were taken from publications indexed on Google Scholar between 2014 and 2024, with a total of 100 identified articles. The results of the analysis showed that 2016 was the year with the most publications, reaching 16 articles, while 2024 recorded the lowest number of publications with only 2 articles.Through network visualization, 25 variables grouped in 5 clusters were found, indicating a significant relationship between research topics. Overlay analysis and density visualization indicate that in 2021, the focus of research is centered on analysis variables, which indicates that this topic has been extensively researched. In addition, bibliometric analysis also revealed that TPACK has a significant impact in the development of research in the field of education, especially in preparing technology-based teaching modules. The methods used in this study include data collection using Publish or Perish application, data processing with Microsoft Excel, and computational mapping using VOSviewer. The results of this study are expected to provide new insights for researchers and education practitioners in integrating technology into the learning process. Thus, this study not only contributes to the development of TPACK theory, but also provides practical guidance for teachers in improving the quality of learning in the digital age.